Kepemimpinan Perempuan dalam Ranah Publik: Analisis Kritis Dalam Pespektif Fikih Siyasah dan Maqashid Syariah - Erly Sulistiyawati; Akhmad Zaki Yamani (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The debate over women's leadership in public office remains a persistent theme in Islamic discourse, spanning both classical and contemporary perspectives. Classical Islamic political jurisprudence (fiqh siyasah) predominantly restricts the highest leadership roles—such as head of state or political leader—to men, rooted in normative textual interpretations and the patriarchal sociocultural context of earlier times. However, contemporary approaches such as maqāṣid al-sharīʿah offer a more inclusive and contextual framework, emphasizing principles of public interest (maṣlaḥah), justice, and individual capability, irrespective of gender. Through a comprehensive literature-based analysis, this study re-examines traditional viewpoints in light of maqāṣid principles and argues that women's involvement in public leadership aligns with the higher objectives of Islamic law. The findings support the urgency of reconstructing Islamic legal thought in a more progressive and contextual direction—one that is capable of addressing modern social dynamics and eliminating gender-biased interpretations. This study thus contributes to the development of a more equitable and inclusive vision of Islamic governance.